Dampak Penggunaan Gadget terhadap Moral dan Etika Peserta Didik di MI Plus Nurul Fattah Gembleb Trenggalek (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
Gadgets are a collection of electronics that are intended to facilitate human tasks and activities, including smartphones and laptops. Gadgets are digital technologies that function as communication and information tools. Not only adults, teenagers, even children have also used gadgets to meet their needs. This study aims to reveal the influence of gadgets on students' morals and ethics. The research method used by the author is a qualitative method with a case study and interview approach. Qualitative research is a type of research that produces findings that cannot be achieved using statistical procedures or other quantification methods. Qualitative research is descriptive and tends to use analysis with an inductive approach. The sample of this study was students in grades 2 and 3 at MI Plus Nurul Fattah Gembleb. The number of students in grade 2 was 29 students and in grade 3 was 28 students. The research was conducted at MI Plus Nurul Fattah Gembleb, Pogalan District, Trenggalek Regency, East Java. The results of the study showed that the use of gadgets in children is in the high category with a percentage of 45.35%, the use of gadgets in children is in the medium category with a percentage of 35.00%, the use of gadgets in children is in the low category with a percentage of 19.65%. The use of gadgets has a significant influence on the development of morals and ethics of students at MI Plus Nurul Fattah. Excessive use of gadgets without proper supervision can have a negative impact on student behavior, such as reduced respect for parents, teachers, and friends. Uncontrolled addiction to playing gadgets can also reduce students' ability to interact socially, reduce empathy levels, and increase the tendency for individualistic behavior, students become lazy to learn and follow learning.